Experience in family planning and public health in Chile - Adriazola E., Guillermo (2015)
I would like to discuss this morning, the experiences we've had since 20 years ago on family planning, public health activity that the country has given us. Because having much in common with their countries, can serve many of you as an element of judgment to overcome negative experiences and be humble in the positive.